Increasing Quantity and Quality of Student’s Question through Problem Based Learning in Biology at Grade X IIS 4 of SMA Negeri 5 Surakarta - Sabila, Wahdania Nuris; Widoretno, Sri; Nurmiyati, Nurmiyati; Sajidan, Sajidan; Ramli, Murni; Ariyanto, Joko (Universitas Sebelas Maret, 2015)
The purpose of this research is to improve quantity and quality of student’s question through problem based learning in biology at grade X IIS 4 of SMA Negeri 5 Surakarta. The research was 4 cycles action research that conducted in academic year 2014/2015. Data were collected through observation, interview and video recording, and validated using triangulation method. Quantity of question collected by counting the number of questions during the learning process. Quality of question categorized based on revised Bloom’s Taxonomy. The result of this research shows: 1) PBL effectively increased the quantity and quality of questions; 2) the quality of student’s question in each cycle at factual, conceptual, procedural dimension. Metacognitiv dimension was identified in the last cycles; 3) the increasing of quantity student’s question from first cycles to the fourth cycles is 156 question at first cycles, 130 question at second cycles, 136 question at fthird cycles and 226 question at fourth cycles.Keywords: quantity and quality of student’s question, problem based learning